KEHIDUPAN SOSIAL EKONOMI PEKERJA TAMBANG EMAS NAGARI KOTO BARU KABUPATEN SIJUNJUNG (2003-2013) - Hartati, Sri; Husnita, Liza; Erawati, Meri (Pendidikan Sejarah, 2013)
ABSTRACTÂ People Gold Mine in Nagari Koto Baru started in the open in 2003, where at that time people began to try other jobs in addition to farming which is the majority of people work in this area for the purpose of seeking other income as family subsistence. In the beginning of gold mining is done in the land of the people by the people who make a living on the side that ultimately made the principal livelihood because it can result in gold from the mine is better than the people who rely on income from agricultural income and plantation. The first aim of this thesis, describing gold mining Nagari Koto Baru second, describing the Socio-Economic Life Gold Mine Workers In Nagari Koto BaruSijunjung district during the years 2003-2013.The method used in this paper is the historical method with the following steps : Heuristics (collection of sources that need to be in writing), source criticism, and interpret the data, and then pour it in writing in the scientific history of the call with Historigrafi.Based on the research that has been carried on it can be concluded that, the gold mining activities in the people who run the society has been able to sustain the local economy, but not evenly. Mining here including categories of illegal mining without government permission, which was known by the term (PETI) and mining here very damaging to the environment and sustainability Sijunjung Nagari Koto Baru district.Â Key word :Socio-Economic, Gold Mine, Workers